Improving mental health response in earthquake-prone regions: recommendations following the recent earthquake in Türkiye - Ramalho, Rodrigo; Ersönmez, Rojda; Kına, İdil; Keçeci, İrem; Apparao, Ramin; Koh, Eugene B.Y.; Coskun, Bülent (Cambridge University Press, 2024)
We are members of Students’ Education, Empowerment and Development in Mental Health, a group of medical students and psychiatrists from around the globe under the Psychiatry, Medicine and Primary Care Section of the World Psychiatric Association. In this article, we put forward recommendations to help improve the mental health response in disaster-prone regions such as Türkiye. We recommend a three-step multi-tiered mental health response system that could significantly help to address the immediate, short-term and long-term mental health needs of communities directly affected by a disaster. The recommendation draws from the relevant literature and, most importantly, from our lived experiences of living in earthquake-prone countries.